Modern weapons and military equipment for issue 3-2017 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2017)
Wireless Technology Brings Crosshair from Thermal Sights to Night Vision Goggle Display; More bang for Bundeswer behemonts; The F-35 Stealth Fighter May Never Be Ready for Combat.